Ovarian mucinous cystadenofibroma: a case report - Jain, Amrita; Kurkal, Nidhi; Gupta, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian adenofibroma is a rare benign tumour originating from the stroma and germinal lining of the ovary. We describe here the case of a 54-year-old female with an ovarian mucinous cystadenofibroma that was diagnosed as a cystic mass of the ovary with neoplastic etiology before surgery. The tumour was a large cystic mass of size 30×25×10 cm arising from left ovary. The patient successfully underwent exploratory laparotomy with excision of large ovarian mass f/b total abdominal hysterectomy with B/L salpingoopherectomy.